EVALUASI PELAKSANAAN PEMBELAJARAN BAHASA JAWA SMA SEBAGAI MUATAN LOKAL DI JAWA TENGAH - Endang Kurniati; Esti Sudi Utami (Jurnal Penelitian Pendidikan, 2010)
The Javanese learning activities have many weakness which come from the teachers, students, and learning materials. From the teachers, more than 60% the teachers are not professional because they don‟t graduate from the Javanese Language. They are still less experience in Javanese teaching. From the student, they are not interested in learning Javanese language. They look down the Javanese language. As the impact of this is that the students are not competence. From the learning materials, there is no Javanese curriculum which was arranged based on need analysis. In the syllabus, there are some mistakes, mainly in developing Basic Competence, Indicators, Life skills, Learning experiment, and valuation. The teachers have difficulties in developing the curriculum, choosing he teaching method, choosing materials, making learning media, and arranging evaluation. Learning Javanese language is not satisfied, because students‟ competence are still under KKM, the students are not interested in learning. The Suggestion in learning Javanese language: Teachers suggest to be held workshop, seminars, the references are available, and learning media are available. The Students suggest that learning Javanese will be interesting if to be given in simple language (familiarly), and learning materials familiarly. Keywords : Javanese language,